KAJIAN BIAYA PRODUKSI, HARGA POKOK DAN BATAS KEUNTUNGAN PADA PENGOLAHAN PRODUK BERSAMA PENGERJAAN KAYU - Setiasih lrawati; l M Sulastiningsih; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1995)
The study on production  cost,  base price  and profit  margin was conducted in wood  working  industry  using  sawn  timber  of perupuk  (Lophopetalum spp.), meranti (Shorea spp.),   damar (Agathis  spp.)  and jangkang  (Xylopia spp.) for various joint  products. The products  were moulding, S4S. Solid  jointed  board, finger jointed board,  finger jointed stick and door jamb. There were five products of perupuk,  two of meranti, two of'jangkang and one of damar.The results of tire  study showed that  the method of joint  cost calculation used  by  the  mill was  average  cost per  unit method. Production  costs  of  jangkang  and damar  wood  working products  were higher  than  those  of  meranti  and perupuk.  The average  proponion  of  raw materials, wages and others on the total production cost was respectively 62%, 4/% and 34%. Proportion  of wage cost was small,  on the contrary, proportion of other production cost was relatively high. Among ten kinds of wood working joint products,  only three yielded  a positive profit margin,  namely,  moulding,  S4S and finger jointed board of perupuk.Based on the average cost per unit method the raw material cost, production cost and base price of S4S were lower than those of finger jointed stick. This results was irrational since the raw  material  cost  of  S4S  should   be  more  expensive  than  that  of finger jointed  stick. Consequently,  the average cost per unit method was not suitable for joint  cost  distributing method of  wood working joint  products.   Therefore.  it is suggested for replacing this method with one that considers quality and price of raw material and the product selling price.